Evaluation of Mediolaterally Distance of Maxillary Sinus Using Cone Beam Computed Tomography - Ali Nooraei Sefid Dashti; Mahdi Abrishami; Azar Eslami; Hamid Bashiri (Isfahan University of Medical Sciences, 2023)
Nowadays, implant-based treatment of edentulous areas has gained significant popularity. However, in many patients who have been edentulous for a long time, changing the position of the sinus causes complications during implant placement, which is necessary to solve Many of these cases can be moved to the required extent with different techniques. This study aims to evaluate the mediolateral distance of the maxillary sinus using Cone Beam Computed Tomography(CBCT).Materials & Methods:This observational-cross-sectional study of 160 patients who needed CBCT imaging were selected from among those referred to the radiology department of Isfahan Islamic Azad University. A sagittal section of the middle part of each missing tooth was selected to measure the mediolateral sinus distance (sinus width). In the selected sagittal section, the residual ridge height and sinus width were measured at 5, 10-and 15-mm height from the alveolar crest. The data were analyzed using the paired t-test and Man-Whitney(p value< 0.05).Results:The average sinus width in women was greater than that inmen atthe 5 and 15 mmintervals, and in the interval of 10 mm, the sinus width in women was less than that inmen. The average residual ridge for women and men was equal to 9.69and 8.27, respectively, which indicated that the amount of residual ridge was higher in women, but this difference was not significant. The premolar area exhibited the highest remaining ridge height, while the first molar area had the lowest.Conclusion:As we move from premolars to molars in edentulous areas, the maxillary sinus tends to widen, and also, the less the remaining ridge is, we may encounter the sinus at a lower level.